2003
DOI: 10.1248/bpb.26.573
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Radioactive Residues Arising from Radiolabel Instability in a Multiple Dose Tissue Distribution Study in Rats

Abstract: Our study objectives were: To quantitatively determine the effect of radiolabel instability on terminal phase radioactive tissue residues in a multiple dose tissue distribution study. To quantitatively compare tissue residue artifacts (non drug-related radioactivity) from two chemically-distinct radiolabel locations. To conduct a definitive multiple dose tissue distribution study using the better of the two radiolabeled compounds. We compared the excretion and tissue distribution in rats of [(14)C]linezolid, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Mass balance studies performed with other antibiotics have identified limited tissue distribution of dalbavancin, linezolid, and tedizolid (8, 9, 12, 19), more prominent urinary elimination of delafloxacin, linezolid, and telavancin (9, 10, 20), and the presence of metabolites of delafloxacin, solithromycin, and telavancin (10, 20, 21). All these factors may impact on the efficacy, safety, and tolerability profile of any antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…Mass balance studies performed with other antibiotics have identified limited tissue distribution of dalbavancin, linezolid, and tedizolid (8, 9, 12, 19), more prominent urinary elimination of delafloxacin, linezolid, and telavancin (9, 10, 20), and the presence of metabolites of delafloxacin, solithromycin, and telavancin (10, 20, 21). All these factors may impact on the efficacy, safety, and tolerability profile of any antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…Piperacillin-tazobactam, tigecycline, linezolid, vancomycin, rifampicin, and imipenem all inhibited P. acnes isolates at MIC below resistance breakpoints. All except vancomycin is demonstrated to penetrate well into prostate (36,(39)(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%